A TOOL FOR THE AUTOMATIC DESIGN OF ELECTRONIC CONTROL SYSTEMS AND CIRCUITS FOR MANUFACTURING PLANTS - Lamas, A.; Duro, R. R. (International Journal of Computing, 2014)
In this paper we have developed a tool for automatically designing distributed digital circuits for the control of all the elements in a manufacturing plant. These circuits can be implemented as traditional boards or programmed into the controllers of the machinery present. The tool is based on evolutionary techniques and provides a way to obtain the best set of controllers for the different elements in the plant using as evaluating criteria parameters related to the global operation of the plant and not to particular parameters of the electronic circuits or individual controllers. These parameters may be productivity, cost, or any other ratio having to do with the real operation of the business. In this work we have extended the evolutionary methodologies in order to be able to design, at the complete system level, combinations of low level systems (digital electronic circuits) without any direct specification of their input/output relationships but rather taking into account the plant they are going to be working in and the high level constraints imposed on the whole system. The resulting tool has been tested in a real kitchen furniture manufacturing plant using as test bench the lacquering line within the plant.